2004
DOI: 10.1191/1352458504ms1023oa
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of multiple sclerosis cerebrospinal fluid

Abstract: Two-dimensional gel electrophoresis and peptide mass fingerprinting were used to identify proteins in cerebrospinal fluid (CSF) pooled from three patients with multiple sclerosis (MS) and in CSF pooled from three patients with non-MS inflammatory central nervous system (CNS) disorders. Resolution of CSF proteins on three pH gradients (3-10, 4-7 and 6-11) enabled identification of a total of 430 spots in the MS CSF proteome that represented 61 distinct proteins. The gels containing MS CSF revealed 103 protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
166
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 16 publications
8
166
0
3
Order By: Relevance
“…Prior proteomic investigations utilizing 2-DE and MALDI-TOF-MS have identified individual proteins present in the CSF of specific diseases, such as Alzheimer's disease, Parkinson's disease, CJD, chronic pain, and primary CNS neoplasms [15,26,[27][28][29]. However, direct comparisons of CSF protein alterations across CNS disease states have not been adequately undertaken, raising legitimate questions regarding the specificity of these CSF markers [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior proteomic investigations utilizing 2-DE and MALDI-TOF-MS have identified individual proteins present in the CSF of specific diseases, such as Alzheimer's disease, Parkinson's disease, CJD, chronic pain, and primary CNS neoplasms [15,26,[27][28][29]. However, direct comparisons of CSF protein alterations across CNS disease states have not been adequately undertaken, raising legitimate questions regarding the specificity of these CSF markers [30].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we found that cystatin C was present in the large majority of nondiagnostic and reactive/inflammatory samples, with the highest-intensity bands noted in inflammatory disease. Others have demonstrated increased expression of cystatin C in inflammatory, infectious, and degenerative CNS diseases, raising the possibility of it use as a marker of non-neoplastic CSF [18,27,28], while two independent studies have yielded conflicting results regarding cystatin C as a diagnostic marker in pain syndromes [31].…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, a number of studies have applied a variety of novel proteomic approaches to the global analysis of biological fluids obtained from affected individuals including plasma and especially CSF. The overall goals of such studies were to create a databank of proteins found in the CSF of multiple sclerosis patients [43] and identify proteins that are uniquely detected in multiple sclerosis as compared to controls [28,44]. However, the search for unique disease markers by the analysis of the CSF presents multiple challenges.…”
Section: Challenges In the Proteomic Analysis Of The Csf From Multiplmentioning
confidence: 99%
“…A number of studies have used proteomic approaches in order to define the protein composition or identify differentially expressed proteins in the CSF of multiple sclerosis patients [28,43,44]. One of the investigations by 2-DE and MS compared CSF obtained from three multiple sclerosis patients with that of three individuals affected by other inflammatory conditions, two with CNS sarcoid and one with viral meningitis [28].…”
Section: Proteomic Analysis Of the Csf Obtained From Multiple Sclerosmentioning
confidence: 99%
See 1 more Smart Citation